Development of a Citizen Science Project-Based Teaching Module to Improve Creative Thinking and Collaboration Skills on Ecology and Biodiversity Materials - Ahmad Rasyid Ridho Agus; Lufri Lufri; Fitri Arsih; Muhyiatul Fadilah; Ahmad Rasyid Ridho Agus; Lufri; Fitri Arsih (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Creative thinking and collaboration skills are important 21st-century competencies that need to be developed through science learning. However, observations in junior high schools in West Pasaman, Indonesia show that students' creative thinking skills are still low with an average of 47.875%, while collaboration skills have not developed optimally because there are still passive students in discussion and group work activities. This study aims to produce a valid, practical, and effective Citizen Science Project-based teaching module to improve students' creative thinking and collaboration skills in Ecology and Biodiversity material. This study is a research and development (R&D) using the Plomp model with research subjects of grade VII junior high school students. Data were collected through validation sheets, teacher and student practicality questionnaires, creative thinking skills tests, collaboration skills questionnaires, and observation sheets. Data analysis was carried out descriptively using percentages and inferential analysis through normality tests, homogeneity tests, Normalized Gain (N-Gain), and Independent Samples t-tests. The results of the study showed that the Citizen Science Project-based teaching module had a validity level of 92.88% with a very valid category, teacher practicality of 99% and student practicality of 92.25% with a very practical category. The module was also quite effective in improving creative thinking skills with an N-Gain value of 64.24% and had a positive influence on collaboration skills with a score difference of 12.56 on the questionnaire and 12.17 on the observation sheet between the experimental class and the control class. Thus, the Citizen Science Project-based teaching module is worthy of being used as an alternative science teaching material to improve students' creative thinking and collaboration skills.